2018
DOI: 10.1021/acsbiomaterials.7b01032
|View full text |Cite
|
Sign up to set email alerts
|

Nanohydroxyapatite/Graphene Nanoribbons Nanocomposites Induce in Vitro Osteogenesis and Promote in Vivo Bone Neoformation

Abstract: Nanomaterials based on graphene oxide nanoribbons (GNR) and nanohydroxyapatite (nHAp) serve as attractive materials for bone tissue engineering. Herein, we evaluated the potential of nHAp/GNR toward in vitro analysis of specific genes related to osteogenesis and in vivo bone regeneration using animal model. Three different concentrations of nHAp/GNR composites were analyzed in vitro using a cytotoxicity assay, and osteogenic potential was determined by ALP, OPN, OCN, COL1, and RUNX2 genes and alkaline phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…However, to eliminate mechanical weaknesses, researchers have used different reinforcing materials. Among the materials used, carbon nanomaterials such as carbon nanotubes (CNTs), graphene, graphene oxide, and graphene nanoribbons (GNRs) have received more attention than others [30][31][32]. The most important reason is the biocompatibility and high mechanical properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, to eliminate mechanical weaknesses, researchers have used different reinforcing materials. Among the materials used, carbon nanomaterials such as carbon nanotubes (CNTs), graphene, graphene oxide, and graphene nanoribbons (GNRs) have received more attention than others [30][31][32]. The most important reason is the biocompatibility and high mechanical properties of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Rodrigues et al 15 characterized the chemical, structural, and biological properties of different concentrations of nHAp/GNR and used simulated body fluid to evaluate their bioactivity and human osteoblasts (bone-forming cells). Recently, Medeiros et al 18 showed that nHAp/GNR induced in vitro and in vivo osteogenesis process after 15 days. However, an understanding of the influence of nHAp/GNR on bone regeneration using an in vivo model has not yet been reported, and is imperative for determining the potential benefits of these composites for treating osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…First, nanoparticles were prepared containing different amounts of nHAp and GNR. Our group has expertise in obtaining non-cytotoxic, bactericide, and in vitro and in vivo osteogenic GNR, using a simple acid and oxygen plasma exfoliation of MWCNTs [ 25 , 26 , 27 ]. Biocompatible and with osteogenic properties nHAp/GNR nanoparticles were also developed by our group using a simple wet chemical ultrasound assisted method [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%